Dynamic wake of a square cylinder controlled with steady jet positioned at the rear stagnation point. (1st August 2021) - Yu, Haiyang; Chen, Wen-Li; Huang, Yewei; Meng, Hao; Gao, Donglai
Abstract: We experimentally investigated the dynamic wake evolution of flow around a square cylinder controlled with steady jet ejecting from the rear stagnation point in a wind tunnel at Reynolds number of 1.33 × 10 4 . For diversified jet momentum coefficients C m, modal analyses, dynamic vortex shedding process, time-averaged turbulence kinetic energy (TKE) and Reynolds shear stress (RSS) were obtained from high-speed Particle Image Velocimetry (PIV) measurements, proper orthogonal decomposition (POD) and dynamic mode decomposition (DMD) analyses. As C m grew, it was found that TKE distribution was restrained and RSS was shifted towards the outlet of the steady jet. Variations of dominant frequencies in POD and DMD modes were observed. The pattern of vortex shedding from the shear layer were transferred from antisymmetric to a symmetric one. The vortex sheets were also observed to be elongated downstream in the wake. Experimental results indicated that the dynamic wake of the square cylinder could be controlled significantly by the steady jet from the rear stagnation point. Highlights: The flow around a square cylinder is controlled with steady jet positioned at its rear stagnation point. The nondimensional jet momentum coefficient is found to play an important role in flow control effectiveness. Steady jet stabilizes the dynamic wake and alleviate the unsteady vortex shedding from the square cylinder.